Analysis of Internal Factors in Improving Perceptions of the Quality of Financial Reports at DPMPD Kediri Regency - Sandia Eka Efilia; Arisyahidin Arisyahidin; Nisa Mutiara (Jurnal Proaksi, 2025)
Abstract Main Purpose -  This research aims to analyze the internal factors that influence the perception of the quality of financial reports in the Regional Work Unit of the Community Empowerment and Village Government Service (DPMPD) of Kediri Regency. Method -  This research uses a qualitative approach with data collection techniques through interviews, observation, documentation, and Focus Group Discussion (FGD). Data analysis was carried out using a qualitative descriptive approach to interpret the meaning of field findings. Main Findings -  Consistent implementation of Government Accounting Standards (SAP) is the main basis for improving the perception of the quality of financial reports. Human resource competency, internal control systems and independent audit results also strengthen confidence in the accountability of financial reports. The main obstacles were found to be the lack of continuous training and weak implementation of comprehensive internal control. Theory and Practical Implications -  This research provides important recommendations for increasing human resource capacity through regular training and strengthening the internal control system to achieve transparency and accountability. These results can also be used as a reference for policy makers in determining public financial management strategies. Novelty -  This research offers a new perspective regarding the perception of the quality of financial reports based on internal factors of local government organizations in depth through a qualitative approach.